Australian consensus guidelines for the safe handling of monoclonal antibodies for cancer treatment by healthcare personnel. Issue 10 (October 2014) - Alexander, M.; King, J.; Bajel, A.; Doecke, C.; Fox, P.; Lingaratnam, S.; Mellor, J. D.; Nicholson, L.; Roos, I.; Saunders, T.; Wilkes, J.; Zielinski, R.; et al.
Abstract These consensus guidelines provide recommendations for the safe handling of monoclonal antibodies. Definitive recommendations are given for the minimum safe handling requirements to protect healthcare personnel. The seven recommendations cover: (i) appropriate determinants for evaluating occupational exposure risk; (ii) occupational risk level compared with other hazardous and non‐hazardous drugs; (iii) stratification of risk based on healthcare personnel factors; (iv) waste products; (v) interventions and safeguards; (vi) operational and clinical factors and (vii) handling recommendations. The seventh recommendation includes a risk assessment model and flow chart for institutions to consider and evaluate clinical and operational factors unique to individual healthcare services. These guidelines specifically evaluated monoclonal antibodies used in the Australian cancer clinical practice setting; however, the principles may be applicable to monoclonal antibodies used in non‐cancer settings. The guidelines are only applicable to parenterally administered agents.